Trade Facilitation and Paperless Trade Implementation - United Nations (United Nations, 2018)
The United Nations Regional Commissions, in partnership with other key United Nations Organizations, have committed to supporting member States in implementing the WTO Trade Facilitation Agreement (TFA). This report is part of that commitment and the policy recommendations and technical standards developed by UNECE and UN/CEFACT are key implementation tools not only for the UNECE region, but also for other regions across the world. The second UNECE Report on Trade Facilitation and Paperless Trade sheds light on the TFA implementation in North American, European and Central Asian countries, identifies best practices, and encourages better cooperation. Government officials and private sector actors involved in trade facilitation reform efforts will benefit from it.